The role of implicit theories in the formation of expert opinion in portuguese criminal law - Da Silva Guerreiro, Joao (2015)
Tese de doutoramento, Ciências e Tecnologias da Saúde (Medicina Legal e Ciências Forenses), Universidade de Lisboa, Faculdade de Medicina, 2014